2019
DOI: 10.1038/s41598-019-45061-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals novel insight on dormancy of aquatic invertebrate encysted embryos

Abstract: Numerous aquatic invertebrates survive harsh environments by displaying dormancy as encysted embryos. This study aimed at determining whether metabolomics could provide molecular insight to explain the “dormancy syndrome” by highlighting functional pathways and metabolites, hence offering a novel comprehensive molecular view of dormancy. We compared the metabolome of morphologically distinct dormant encysted embryos (resting eggs) and non-dormant embryos (amictic eggs) of a rotifer ( Brachionus pli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 83 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Trehalose is known to accumulate in diapausing cysts of Artemia 45 , 46 and in diapausing rotifer eggs when they enter anhydrobiosis 47 . Transcripts encoding for trehalose-6-phosphate synthase and for trehalose phosphate synthase enzymes have been detected in diapausing rotifer eggs, suggesting its biosynthesis in rotifers 23 , 25 , 34 G protein-coupled receptor signalling pathway (17/206) G protein-coupled receptors (GPCR) regulate signal transduction pathways and play diverse and pivotal roles in the physiology of insects, especially in resistance to adverse environmental conditions 48 . Interestingly, a GPCR receptor in the silkworm, B. mori , has been identified as a specific cell surface receptor for the diapause hormone (DH) 49 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Trehalose is known to accumulate in diapausing cysts of Artemia 45 , 46 and in diapausing rotifer eggs when they enter anhydrobiosis 47 . Transcripts encoding for trehalose-6-phosphate synthase and for trehalose phosphate synthase enzymes have been detected in diapausing rotifer eggs, suggesting its biosynthesis in rotifers 23 , 25 , 34 G protein-coupled receptor signalling pathway (17/206) G protein-coupled receptors (GPCR) regulate signal transduction pathways and play diverse and pivotal roles in the physiology of insects, especially in resistance to adverse environmental conditions 48 . Interestingly, a GPCR receptor in the silkworm, B. mori , has been identified as a specific cell surface receptor for the diapause hormone (DH) 49 .…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence of K + -mediated stimulation of aminoacyl-tRNA (aa-tRNA) synthetase activity in bacteria 54 and insects 55 , with an effect on diapause termination in the latter. Rozema et al 25 have shown high levels of aa-tRNA synthetases in diapausing compared to asexual eggs in Brachionus Ion transmembrane transport (16/147) Free ions in the cytosol restart the cell machinery by reactivating cellular enzymes 56 . Dumont et al 57 showed that cyst hatching in some anostraceans increased after the addition of mobile ion carriers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations